Schizofrenia, substance use and aggressions: what are the relationships? - Rashid, R.A.; Robson, N.Z.; Sulaiman, A.H.; Salleh, R.; Zainal, N.Z.; Said, M.A.; Habil, M.H. (ASEAN Federation of Psychiatry and Mental Health (AFPMH), 2010)
Objectives: The objective of the study is to determine the prevalence of substance abuse for alcohol, cannabis, opiates, stimulants, solvent and other substances among patients with schizophrenia in Hospital Bahagia Ulu Kinta (HBUK), Perak , Central Peninsular of Malaysia. This study also aims to determine the association of substance abuse with aggression, the demographic characteristics and total duration of hospitalization. Methods: This was a retrospective cross-sectional study whereby the first 194 subjects diagnosed to have schizophrenia based on International Classification of Disease, 10th edition (ICD-10) criteria were taken from data registry of patients admitted to HBUK from January until February 2004. The subjects’ medical files were examined for documentation of substances abuse, aggression and accumulative duration of hospitalization. Results: The results showed the prevalence of substances misuse among patients with schizophrenia in general (including alcohol) was 24.7%. Cannabis 16.7%, alcohol 13.4%, opiates(heroin) 6.7%, Amphetamine type stimulants (amphetamine, metamphetamine, ecstacy) 5.7%, and other substances (benzodiazepine, solvents) 1.5%. Conclusion: There is higher prevalence of substance misuse in patients with schizophrenia as compared to general population. Male patients with history of substance misuse are more likely to have aggression than female. This group needs special precaution and probably in need of specialist help.